CFG Pile Composite Foundation: Its Engineering Applications and Research Advances - Bantayehu Uba Uge; Yuan-Cheng Guo (Journal of Engineering)
Problematic soils exist almost everywhere on the globe. State-of-the-art solutions to make civil engineering infrastructures built on them are still highly sought. The CFG (cement-fly ash-gravel) pile composite foundation system has been widely used in buildings, highways, railways, and bridge transition sections owing to its proven engineering characteristics in soft ground treatment. This paper discusses about the development and achievements of its engineering applications, along with possible future research directions. The remarkable evolution took place in the past to address projects’ strict differential and postconstruction settlement control requirements including embedding the geosynthetic layer into the load transfer platform and combining it with rigid slabs, as seen implemented in few CFG pile-supported embankments. It was also observed that the interaction of the existing CFG pile composite foundation with an adjacent new foundation pit excavation inevitably presents a complex soil-structure interaction mechanism among the fundamental components—the retaining wall, mat, piles, cushion, and soil.